India : Investment Climate and Manufacturing Industry - World Bank (Washington, DC, 2013)
Differences in the investment climate have recently gained centre stage in explaining variations in competitiveness, growth and prosperity across countries or regions. The investment climate comprises institutional and policy variables that have a crucial bearing on business performance, but over which firms have no control individually. Key determinants of the investment climate include the functioning of product and factor markets; sources of non-pecuniary intra- and inter-industry externalities (i.e., spillovers) the quality of public goods (such as law and order, government regulation) and their effects on the cost of borrowing, on price stability, or on exchange rates via fiscal and monetary policies; and some physical and social infrastructure. The report asseses India's investment climate from the perspective of industrial growth and focuses on investment climate variations within India, analyzing the implications these variations have on industrial performance, as well as, subnational disparities in productivity and growth.